Hydaticus (Prodaticus) kourouensis sp. n., a new diving beetle species from French Guiana (Coleoptera: Dytiscidae). Issue 3 (2nd July 2020) - Hendrich, Lars; Balke, Michael
Abstract: We discovered a new species of the genus Hydaticus Leach, 1817, subgenus Prodaticus Sharp, 1882 (Coleoptera: Dytiscidae) in the unidentified material of the Muséum National d´Histoire Naturelle, Paris. The type specimens were collected near Kourou in French Guiana and are here described as Hydaticus ( Prodaticus ) kourouensis sp. n. The new species is morphologically similar to the Peruvian H. panguana Megna, Balke, Apenborn, and Hendrich, 2019 and H. hauthi Hendrich and Balke, 2020, but differs by its almost complete black ventral surface, the broadly oval habitus, and the flattened, slightly enlarged elytra. Furthermore, H. kourouensis sp. n. is well characterised by the shape of its median lobe. http://www.zoobank.org/urn:lsid:zoobank.org:pub:E0841C37-DB18-45E3-80B8-2981E63CCCA2